Hydrological responses to the synergistic climate and land-use changes in the upper Lancang river basin - Mingyue Xie; Yu Li; Ximing Cai (Environmental Research Letters, 2023)
Climate change trends in the upper Lancang river basin (LRB), a high-mountain area, are prominent on a global scale, and climate-induced land use change with increasing cropland and migration has been observed in the past decades and is expected to expand in the future. We assessed land use and sediment yield from the basin in the past and future under the synergistic impact of projected climate change and associated land use change. We found that the transition from grassland and forest to cropland under climatic change favorable to agriculture can be the topmost contributor to the sediment yield increase from the upper LRB, with an increaisng rate of 40.6% from the entire area and as high as 118% in some sub-areas. As the baisn serves as the source area of the Lancang-Mekong River Basin (LMRB), we call for coordinated management throughout the entire LMRB, given the complex sediment dynamics crossing scales, affected by both climate change and socioeconomic development in trans-boundary basin.